LOCAL E-CATALOG 5.0 PROGRAM AS A STRATEGY TO CREATE A CREATIVE ECONOMY AND INCREASE LOCAL TOURISM IN INDONESIA - Utami, Eva Yuniarti; Hanasi, Raihan A.; Putra, Johni Eka; Afrizal, Afrizal; Kalalo, Rieneke Ryke (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is a qualitative research with a descriptive approach that is closely related to E-Catalog and its role in developing tourism in Indonesia. The data used in this article are secondary data that researchers obtain from scientific articles, books, scientific magazines, and a number of other sources related to this topic. The data are collected, selected, and analyzed using the SWOT analysis method which is explained in the following sections. The result in this article show that E-Catalog has many benefits in developing tourism in Indonesia, especially if E-Catalog can go hand in hand with existing technological advances. The benefits in question are that it can increase the quantity of visitors, the finances of tourist attractions, and so on. In contrast to the points mentioned above, the implementation of E-Catalog also has a number of weaknesses and threats, namely, uneven Human Resources, programs that are not running, and capital losses. Keywords: E-Katalog, Local Tourism, Creative Economy